Current Immunotherapy Approaches in Non-Hodgkin Lymphomas - Pytlik, Robert; Polgarova, Kamila; Karolova, Jana; Klener, Pavel (Vaccines, 2020)
Non-Hodgkin lymphomas (NHLs) are lymphoid malignancies of B- or T-cell origin. Despite great advances in treatment options and significant improvement of survival parameters, a large part of NHL patients either present with a chemotherapy-refractory disease or experience lymphoma relapse. Chemotherapy-based salvage therapy of relapsed/refractory NHL is, however, capable of re-inducing long-term remissions only in a minority of patients. Immunotherapy-based approaches, including bispecific antibodies, immune checkpoint inhibitors and genetically engineered T-cells carrying chimeric antigen receptors, single-agent or in combination with therapeutic monoclonal antibodies, immunomodulatory agents, chemotherapy or targeted agents demonstrated unprecedented clinical activity in heavily-pretreated patients with NHL, including chemotherapy-refractory cases with complex karyotype changes and other adverse prognostic factors. In this review, we recapitulate currently used immunotherapy modalities in NHL and discuss future perspectives of combinatorial immunotherapy strategies, including patient-tailored approaches.
Keywords: CAR T-cells; immune checkpoint inhibitors; bispecific antibodies; non-Hodgkin lymphomas; immunomodulatory agents